Pneumonitis in advanced non-small-cell lung cancer patients treated with EGFR tyrosine kinase inhibitor: Meta-analysis of 153 cohorts with 15, 713 patients: Meta-analysis of incidence and risk factors of EGFR-TKI pneumonitis in NSCLC. (September 2018) - Suh, Chong Hyun; Park, Hye Sun; Kim, Kyung Won; Pyo, Junhee; Hatabu, Hiroto; Nishino, Mizuki
Highlights: Incidence of pneumonitis was 1.12% in NSCLC patients without prior EGFR-TKI exposure. Patients from Japan had a significantly increased risk of developing pneumonitis. Results provide insights for risk factors and biomarkers for EGFR-TKI pneumonitis. Abstract: Purpose: Pneumonitis is a significant toxicity of EGFR tyrosine kinase inhibitors (EGFR-TKI) in non-small-cell lung cancer (NSCLC) patients. We studied the incidence of pneumonitis in clinical trials of EGFR-TKI published in 2003–2017, and performed subgroups analyses to identity predisposing factors. Methods: Ovid-MEDLINE and EMBASE search up to 4/17/17 using the keywords, "erlotinib", "gefitinib", "afatinib", "osimertinib", and "lung cancer", resulted in a total of 153 eligible trial cohorts with 15, 713 advanced NSCLC patients treated with EGFR-TKI. The pooled incidence of all-grade, high-grade, and grade 5 pneumonitis was obtained. Subgroup analyses were performed with meta-regression using study-level covariates. Results: Among the patients without prior exposure to EGFR-TKI, the overall incidence was 1.12% (95% CI:0.79–1.58%) for all-grade, 0.61% (95% CI:0.40-0.93%) for high-grade, and 0.20% (95% CI:0.11-0.38%) for grade 5 pneumonitis. The incidence was significantly higher in Japanese studies compared to studies of non-Japan origin, for all-grade (4.77% vs. 0.55%, p < 0.001), high grade (2.49% vs. 0.37%, p < 0.001), and grade 5 pneumonitis (1.00% vs. 0.18%, p < 0.001). Multivariate analyses demonstrated higher odds of pneumonitis in Japanese studies for all-grade (odds ratio [OR]: 5.04; 95% CI:3.14–8.11, p < 0.001), high-grade (OR: 4.45; 95% CI:2.50–7.93, p < 0.001), and grade 5 pneumonitis (OR: 4.55; 95% CI:2.20–9.44, p < 0.001) compared to others, after adjusting for types of EGFR-TKI and lines of therapy. In patients with EGFR retreatment analyzed separately, the pooled incidence was 1.13% (95% CI:0.40–3.15%) for all-grade, 0.49% (95% CI:0.21–1.11%) for high-grade, and 0.16% (95% CI:0.04-0.65%) for grade 5 pneumonitis. Conclusions: The overall incidence of EGFR-TKI pneumonitis was 1.12% in patients without prior exposure to EGFR-TKI, and 1.13% in EGFR-TKI retreatment group. The cohorts from Japan had significantly higher incidence of pneumonitis, providing insights for further mechanistic studies.